The Inspiration Watch: An Augmented Shopping Device - Murphy, Rachel; Sellen, Abigail (Proceedings of Ubicomp, 2002)
The “Inspiration Watch” is a conceptual design for a wirelessly connected watch that displays images on a small, colour LCD screen. The watch is intended to aid shoppers in deciding on gifts to buy for friends and family. The concept was inspired by observations made during a study of consumer’s shopping behaviour. After generating an explanatory animation of the concept, a short study was conducted to gain user feedback.